The cultural references in the narrative of Tawfīq al-Ḥakīm: analysis of translation techniques related to food and clothing - Saad-Helal, Saad Mohamed (Anaquel de Estudios Árabes, 2018)
Our objective is to carry out a quantitative analysis of the translation techniques applied during the transfer to Spanish of the cultural references related to food and clothing in two novels of Tawfīq al-Ḥakīm. Translators offer texts that are not characterized by a large dose of foreignization. There is a balance between the techniques that represent the maximum manifestation of foreignization and domestication: the loan and adaptation. Comparing the data, we observe certain differences between the two translations. Thus, within the techniques of foreignization one of the translators prefers to resort to the loan, while the other opts in favour of the coined equivalent. Regarding the degree of transgression of the forms of expression of the arrival language, we observe an obvious conservative character in Diario de un fiscal rural, against a more daring and transgressor language use in El despertar de un pueblo. The data is in line with what both translators announce in their respective introductions.
Keywords: Cultural references; narrative; Tawfīq al-Ḥakīm; translation